Pelestarian Dan Pengembangan Keanekaragaman Seni Nusantara Bahasan tentang Memajukan Pendidikan dan Menguatkan Karakter - Tjetjep Rohendi Rohidi (Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
Three important cases need to be raised to begin this article. First, it is the issue of advancing education and strengthening culture. The issue should be seen as awareness to understand arts in various archipelago as a whole system, namely regarding human’s behaviour and values and natural-physical and socio-cultural environmental resources; that is, an eco-cultural system. This basic understanding becomes the starting point for carrying out activities or praxis in dealing with the changes which occur. Second, the effort of inheritance in its form as the preservation and development of this culture which refers to the awareness of artistic diversity which needs to be maintained as a system that gives freedom in unity and integrity. Third, art is a cultural element that is sensitive to differences, and becomes a flexible means of bridging differences; it becomes a means of appreciation of the refined inner space to overcome violence, hatred, pride, and greed. In brief, what is discussed in this paper comprises (1) art in Indonesia in the context of the archipelago culture; (2) socio-cultural changes and their implications in the development of art in Indonesia; and (3) inheritance efforts as an educational process which needs to be done. The problem is thoroughly tried to be discussed through an eco-cultural perspective, namely by putting the parts of the problem as a whole system which is interconnected among humans, values, and their environment in the micro and macro environment.